PSIKOTERAPI BERSAMA NABI - Siregar, Muhammad Nuh (Department of Hadis Sciences (IH), Faculty of Usuluddin, Adab, and Da'wah (FUAD), State Islamic Institute of Langsa (IAIN), 2018)
This paper talks about psychotherapy to various psychiatric disorder based on hadith. It was found that many hadith of Rasulullah saw. mentioned the solutions which can be used as therapy to heal various psychiatric disorder. It mentioned that zikr, dua and istighfar may heal hallucinating problem, depression, and ?Gegana?. As stress can be relieved through communicating to God, stubbornness and hard-hearted also healed by seeking for God forgiveness and try to open the heart by doing full submission to Him. As reciting God?s names and calling him continuously may provide the feel of peace and secure, those who tortured by bad tempered or heartbroken may healed by fasting. If these psychotherapy taught by prophet Muhammad were applied consistently, undoubtedly, Muslims will be spared form any psychiatric disorders as mentioned.